Teacher's Perspective On The Impact Of Online English Teaching In Primary School - Abdul Azis Nasution (SNHRP, 2023)
The researchers wanted to analyze teachers' perspectives on the impact of online English teaching in primary schools. This study used a descriptive qualitative method. One of the primary schools participated in the study. Data was collected via interviews with one of the English teachers in elementary school. Based on the findings, it was determined that numerous online learning programs are used by educators in distance learning, including Zoom, Google Sites, Google Meet, WhatsApp, Youtube, and others. The results also show a positive impact of online English teaching, namely, more flexible means that it can be done anytime and anywhere and easy to access, Improve the teacher's cognitive skill to use technology, and save time and can be done anytime. While the negative impacts are; the interaction between teachers and students is reduced lack of student motivation in online learning, lack of quality, limited quota, and disrupted internet network